Thyroid cancer mortality in Brazil and its geographic regions: mortality trends and projections until 2030 - Fernandes, Fábia Cheyenne Gomes de Morais; Soares, Samara Carollyne Mafra; Bezerra, Héllyda de Souza; de Souza, Dyego Leandro Bezerra; Barbosa, Isabelle Ribeiro (Saúde (Santa Maria), 2020)
The objective of this study was to analyze temporal trends for thyroid cancer mortality in Brazil and its geographic regions, in the period 2001-2015, and calculate mortality projections until 2030. Methods: An ecological study is presented herein on thyroid cancer-related deaths in Brazil, based on the registries of the Mortality Information System. Mortality trends were analyzed by Joinpoint regression, and the Nordpred software (within the R program) was utilized for the calculation of projections. Results: An adjusted mortality rate (ASW) of 0.48 deaths/100,000 inhabitants was obtained for women and 0.27 deaths/100,000 inhabitants for men, with a significant decreasing trend for the female sex (APC= -1.6; CI95%: -2.5; -0.6), while for the male sex the mortality rates decreased non-significantly (APC= -0.5; CI95%: -1.5; 0.5). Mortality rates for the female sex present a decreasing projection until 2030. For the male sex, the same characteristic is observed, however the North and Northeast regions present increasing projections, and these numbers are mainly explained by the variation in the Brazilian demographic structure. Conclusions: Thyroid cancer mortality presented decreases, more pronounced for the female sex.